Development of Enhanced Food Packaging Systems based on Blends of Bio-Based and Biodegradable Polymers Exhibiting Antimicrobial Properties - Agboluaje, Aishat (AUC Knowledge Fountain, 2022)
Food packaging is one of the important aspects of food processing, which contributes greatly to decreasing post-harvest food losses. While ensuring that foods are adequately packaged, it is also important to consider the impact of these food packaging materials on the environment. Accordingly, this research work was aimed at investigating the potential of bio-based and biodegradable blends of polyvinyl alcohol (PVA) and chitosan loaded with antimicrobial agents such as turmeric, clove, and cinnamon for use in food packaging applications. The methodology involved creating PVA/chitosan films with varying compositions via solvent casting method and selecting the best composition exhibiting the highest tensile strength, followed by its incorporation with antimicrobial agents. The morphology of the film was investigated via scanning electron microscopy (SEM), which showed mostly homogeneous and compact texture. Interaction between film components was analyzed via Fourier transform infrared spectroscopy (FTIR), which indicated that the incorporation of antimicrobial agents did not alter the structure of the PVA/chitosan films. Thermogravimetric analysis showed that there was no significant effect on the thermal degradation profile of the antimicrobial films when compared with plain film. The mechanical properties of PVA/chitosan films were significantly altered by the addition of antimicrobial agents while antioxidant and antimicrobial activity of the films were enhanced. The shelf life of chicken breast meat and white cheese packaged within these films were investigated via pH and microbiological assay and the results showed effective inhibition against coliform and S. aureus in cheese and chicken breast meat. These results suggest that PVA/chitosan films have a great potential in the food packaging industry.